Chemical mimicry of insect oviposition sites: a global analysis of convergence in angiosperms. (10th July 2013) - Jürgens, Andreas; Wee, Suk‐Ling; Shuttleworth, Adam; Johnson, Steven D.; Gurevitch, Jessica
Abstract Floral mimicry of decaying plant or animal material has evolved in many plant lineages and exploits, for the purpose of pollination, insects seeking oviposition sites. Existing studies suggest that volatile signals play a particularly important role in these mimicry systems. Here, we present the first large‐scale phylogenetically informed study of patterns of evolution in the volatile emissions of plants that mimic insect oviposition sites. Multivariate analyses showed strong convergent evolution, represented by distinct clusters in chemical phenotype space of plants that mimic animal carrion, decaying plant material, herbivore dung and omnivore/carnivore faeces respectively. These plants deploy universal infochemicals that serve as indicators for the main nutrients utilised by saprophagous, coprophagous and necrophagous insects. The emission of oligosulphide‐dominated volatile blends very similar to those emitted by carrion has evolved independently in at least five plant families (Annonaceae, Apocynaceae, Araceae, Orchidaceae and Rafflesiaceae) and characterises plants associated mainly with pollination by necrophagous flies and beetles.